A Practical App for Quickly Calculating the Number of People Using Machine Learning and Convolutional Neural Networks - Ching-Ta Lu; Chun-Jen Ou; Yen-Yu Lu (Applied Sciences, 2022)
Calculating the number of people is often necessary and repeated in real life. As the number of people increases, the calculation is time-consuming. Efficiently calculating the number of people is helpful to human life. In this article, we propose a valuable app to quickly calculate the number of people in a photo by a convolutional neural network (CNN). Initially, suspected face areas are segmented into micro-blocks. The segmented blocks are then confirmed through the CNN by rejecting the segmented micro-blocks without the human face to ensure the detection accuracy of the face area. The experimental results reveal that the proposed app can efficiently calculate the number of people. The world is now seriously threatened by the COVID-19 epidemic. The proposed app can help quickly calculate the number of people, avoid crowd gathering, and cause the risk of group infections.